Nanorobotic manipulation setup for pick-and-place handling and nondestructive characterization of carbon nanotubes - Eichhorn, V.; Carlson, K.; Andersen, K.N.; Fatikow, S.; Boggild, P. (2007 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2007)
A nanorobotic manipulation setup for the handling and characterization of carbon nanotubes (CNTs) is presented. The nanorobotic setup can be integrated into a scanning electron microscope (SEM) and various endeffectors may be attached to the manipulator either for CNT handling or characterization. The pick-and-place task is carried out by using an electrothermal actuated microgripper, designed for controlled manipulation of nanotubes. The nanotube is picked up from an array of multiwalled carbon nanotubes (MWCNTs) and transferred to the tip of an atomic force microscope (AFM) probe in order to assemble a high-aspect ratio AFM supertip. Another application of the nanorobotic setup considered in this paper is the nondestructive mechanical characterization of CNTs. A piezoresistive AFM probe is used to bend MWCNTs, while the bending force is measured, in order to estimate the Young's modulus of the investigated MWCNTs.